Steel-Reinforced Concrete Structures Assessment and Repair of Corrosion, Second Edition. - El-Reedy, Mohamed A. (London, UNITED KINGDOM CRC Press, 2017)
"This book examines the corrosion of reinforced concrete from a practical point of view, highlights protective design and repair procedures, and presents ongoing maintenance protocols. Updated throughout, this new edition adds additional information on concrete repair using Carbon Fiber Reinforced Polymers (CFRP), and reviews new examples of the effects of corrosion on both prestressed and reinforced concrete structures. It also examines economic analysis procedures and the probability of structural failures to define structural risk assessment, and covers precautions and recommendations for protecting reinforced concrete structures from corrosion based on the latest codes and specifications."--Provided by publisher.
Chapter 1 Introduction -- chapter 2 Corrosion of Steel in Concrete -- chapter 3 Causes of Corrosion and Concrete Deterioration -- chapter 4 Assessment Methods for Reinforced Concrete Structures -- chapter 5 Codes and Specification Guides -- chapter 6 Controlling Corrosion in Steel Bars -- chapter 7 Methods for Protecting Steel Reinforcements -- chapter 8 Repair of Reinforced Concrete Structures -- chapter 9 Risk-Based Maintenance Strategy.
OCLC-licensed vendor bibliographic record.